Discriminative Validity of the Dimensional Obsessive–Compulsive Scale for Separating Obsessive–Compulsive Disorder From Anxiety Disorders. (June 2020) - Ong, Mian-Li; Reuman, Lillian; Youngstrom, Eric A.; Abramowitz, Jonathan S.
Objective: We investigated the diagnostic efficiency and clinical utility of the Dimensional Obsessive–Compulsive Scale (DOCS) and subscales for distinguishing obsessive–compulsive disorder (OCD) from anxiety disorders (ADs).Method: A total of 369 participants (167 male, M age = 29.61 years) diagnosed with DSM-IV OCD or AD, recruited from specialty clinics across the United States, completed clinical interviews and self-report questionnaires, including the DOCS. Receiver operating characteristic analyses and diagnostic likelihood ratios (DiLRs) determined discriminative validity and provided clinical utility. Logistic regressions tested for incremental validity in the DOCS-total scale and subscales in predicting OCD status.Results: The DOCS-total scale and Contamination subscale performed best in differentiating between OCD and AD diagnosis (DOCS-total: Area under curve [AUC] = .75, p < .001; Contamination: AUC = .70, p < .001) as compared with the other subscales. At high scores (DOCS-total: 28+, Contamination: 6+), Contamination was more effective than the DOCS-total in differentiating OCD from ADs, with high scores in Contamination quadrupling OCD odds and DOCS-total by about threefold (Contamination DiLR+ = 4.04, DOCS-total DiLR+ = 2.82). At low scores (DOCS-total: 0-9, Contamination: 0-2), the converse was true, with low scores in Contamination cutting OCD odds by half and DOCS-total by one fifths (Contamination DiLR− = 0.52, DOCS-total DiLR− = 0.23).Conclusion: At high scores, the Contamination subscale is the most helpful subscale to differentiate OCD and ADs. For low scores, the DOCS-total scale performs the best among the scales.